Yield loss assessment in rice (Oryza sativa) due to false smut infection - BAITE, MATHEW S; S, RAGHU; R, PRABHUKARTHIKEYAN S; MUKHERJEE, ARUP K; BAG, MANAS K; JENA, MAYABINI (The Indian Journal of Agricultural Sciences, 2020)
Rice false smut caused by Ustilaginoidea virens is a destructive inflorescence disease threatening rice production worldwide. The disease is emerging in many rice growing countries including India. Estimation of yield loss helps to understand the importance of the disease and hence appropriate measures for its management may be devised. Therefore, an investigation was conducted in farmers’ field of Odisha during kharif 2017. The disease incidence, chaffiness and yield loss for 20 rice genotypes were assessed following a standard method. Disease severity was calculated based on the number of smut ball in an infected panicle. False smut incidence varied from 6-33% while the disease severity ranged from 0.33-17.25% in different genotypes. The highest disease incidence was observed in Pooja (33.33%) followed by Varsha Dhan (16.67%) and Sarala (13.89%). The highest disease severity was observed in Pooja (17.25%) followed by Utkal Prava (10.46%) and Moti (8.89%). The healthy panicles have relatively higher weight and number of grain than the smut panicles. The smut panicle contained more number of chaffy grains than the healthy panicle. The yield loss of rice due to false smut infection varied between 0.10-5.14% in different genotypes. Maximum yield loss occurred in Moti (5.14%) followed by Gayatri (4.60%). The finding is significant as it indicates the emergence of false smut as a threat to rice production.